2017
DOI: 10.1158/0008-5472.can-16-3190
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1 Downregulation in Clear Cell Renal Cell Carcinoma Promotes Vascularization and Metastatic Progression

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common type of kidney cancer and it forms highly vascularized tumors. The monocyte endoribonuclease MCPIP1 negatively regulates inflammation by degrading mRNA encoding proinflammatory cytokines, such as IL6, IL1, and IL12. MCPIP1 is also a negative regulator of NFkB and AP1 activity and it influences a broad range of miRNA activities. Here we report that MCPIP1 protein levels are decreased during renal cancer progression. In patientderived tumors and xenograf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 49 publications
4
76
1
Order By: Relevance
“…Emerging evidence has revealed the function of CXCL12-CXCR4 axis in cancer progression, especially regarding tumor metastasis (24)(25)(26). Studies have shown that aberrantly expressed CXCL12 or CXCR4 was correlated with tumor hematogenous spread and prognosis in multiple solid malignancies such as breast cancer, pancreatic cancer, and prostate cancer (24,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has revealed the function of CXCL12-CXCR4 axis in cancer progression, especially regarding tumor metastasis (24)(25)(26). Studies have shown that aberrantly expressed CXCL12 or CXCR4 was correlated with tumor hematogenous spread and prognosis in multiple solid malignancies such as breast cancer, pancreatic cancer, and prostate cancer (24,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that MCPIP1 regulates inflammatory processes by controlling transcripts coding for proinflammatory cytokines, such as IL-1beta, IL-6, IL-12p40, IL-2 and transcription factors controlling proinflammatory processes, such as the c-Rel subunit of NFκB [4][5][6][7]. Furthermore, MCPIP1 regulates processes important in cancer development, such as cell metabolism, proliferation, and angiogenesis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Low MCPIP1 levels have been reported in neuroblastoma [ 12 ], breast cancer [ 13 ] and ccRCC [ 4 , 14 ]. MCPIP1 inhibits growth of ccRCC and neuroblastoma cell lines [ 4 , 12 ] by enhancing the decay of anti-apoptotic gene transcripts, including Bcl2L1, Bcl2A1, RelB, Birc3, and Bcl3 [ 13 ] and negatively regulating the rate of metabolism and angiogenesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%